2010
DOI: 10.1002/lary.20914
|View full text |Cite
|
Sign up to set email alerts
|

Under the microscope: Assessing surgical aptitude of otolaryngology residency applicants

Abstract: The value of applicant screening tests in predicting surgical competency is controversial. We describe a direct assessment tool that may prove useful in identifying outliers, both high and low, to aid in final applicant ranking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…[78][79][80][81][82][83][84] A soap carving task as part of an otolaryngology residency interview was not predictive of cognitive knowledge, visuospatial ability, manual dexterity, decision making, or overall resident performance. 82 The use of surgical skills testing at an otolaryngology residency interview did not correlate with USMLE Step 1 scores, 78 although in a larger cohort, it was predictive of faculty performance evaluation. 79 Assessment of clinical skills in the form of an objective structured clinical examination or a multiple mini interview (MMI) to assess competencies desired by the program has been described for individual programs and regional assessment centers for selection of residents.…”
Section: Clinical and Surgical Skillsmentioning
confidence: 92%
“…[78][79][80][81][82][83][84] A soap carving task as part of an otolaryngology residency interview was not predictive of cognitive knowledge, visuospatial ability, manual dexterity, decision making, or overall resident performance. 82 The use of surgical skills testing at an otolaryngology residency interview did not correlate with USMLE Step 1 scores, 78 although in a larger cohort, it was predictive of faculty performance evaluation. 79 Assessment of clinical skills in the form of an objective structured clinical examination or a multiple mini interview (MMI) to assess competencies desired by the program has been described for individual programs and regional assessment centers for selection of residents.…”
Section: Clinical and Surgical Skillsmentioning
confidence: 92%
“…The final test was a microvascular knot-tying station based on the protocol described by Carlson et al 5 as a ''go, no-go'' evaluation used at their institution. Our modified setup used video-recording equipment and 2 independent reviewers blinded to participants' identities.…”
Section: Methodsmentioning
confidence: 99%
“…There is now evidence that innate psychomotor abilities positively predict both laparoscopic and endoscopic simulator performance. 14,15 In vascular surgery, it has been shown that innate visuospatial and psychomotor abilities accurately predict performance on a virtual reality endovascular simulator. 16 The Royal College of Surgeons in Ireland has recently begun to evaluate both basic surgical skills, including knot tying, suturing, and laparoscopic skills, as well as innate psychomotor, visuospatial, and perception abilities in all candidates for advanced surgical training.…”
Section: Aptitude Testing and Selectionmentioning
confidence: 99%